PENCEGAHAN KERUSAKAN LINGKUNGAN MELALUI INSTRUMEN HUKUM ADMINISTRASI - Erwin Indra Putra (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTAdvances in science and tehknologi rapidly growing in the West since the 17th century has brought a variety of changes in value (value migration) in manusia.Kondisi civilization thus forcing other countries, especially third world countries to pursue world in the development of science and tehknologi             Meanwhile the third world people's lives, is still experiencing a transition from an agrarian society to a life pattern pattern patterned industry masyarakaat life "economical" and very capitalist, in this context that most of the third world countries compete to build the nation with regard nature as a resource or capital construction very profitable so the exploitation of natural resources is done to excess and sometimes forget about the environmental harmony